Risk Perception and Knowledge, Attitudes, and Practices Against COVID-19 in a Hypertensive Population From a Semi-Urban City of Ecuador - Aumala, Teresa; Cardenas, Maria; Vergara, Daniel; Vasconez, Monserrate; Palacios, Ivan; Terán, Enrique (Frontiers in Public Health, 2021)
Background: In an elderly population with hypertension, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is associated with a higher incidence of mortality and a protracted course of clinical symptoms. Objective: To assess the perceived risk of infection and complications due to COVID-19 in people with hypertension living in a semi-urban city of Ecuador. Methods: A cross-sectional telephone survey of adult outpatients with a previous diagnosis of hypertension in the semi-urban community of Conocoto in Quito, Ecuador was conducted from August to December 2020. Results: A total of 260 adult outpatients, aged 34–97 years, completed telephone surveys. Of total, 71.5% (n = 186) of respondents were women and 28.5% (n = 74) of respondents were men. Overall, 18.1% believe that their risk of infection is “very high,” 55.4% believe that their risk of infection is “high,” 21.5% believe that their risk of infection is “low,” and 5% believe that their risk of infection is “very low.” The perceived risk of complications, if infected by COVID-19, revealed that 21.9% believe that their risk of complication is “very high,” 65.0% believe that their risk of complication is “high,” 10.4% believe that their risk of complication is “low,” and 2.7% believe that their risk of complication is “very low.” Conclusion: Patients with hypertension are aware of the risks posed by COVID-19 infection and its impact on their health. However, the health system must educate the population on health practices and behaviors to avoid COVID-19 infection until the majority of the population of Ecuador can be vaccinated.